2016
DOI: 10.1111/mcn.12266
|View full text |Cite
|
Sign up to set email alerts
|

Service‐wide management of healthy gestational weight gain following an implementation science approach

Abstract: The aim of health guidelines is to ensure consistency in the delivery of care to minimise health-related complications. However, even when good evidence is available, professionals do not necessarily implement it. Following a 2011 survey (Time 1) of staff in a tertiary maternity hospital, a number of service changes were implemented to facilitate best practice delivery of care to pregnant women regarding gestational weight gain (GWG). A (second) staff survey was then undertaken to re-assess staff knowledge, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…Two recent papers from the same institution used an implementation science approach to address identified barriers to GWG guideline adherence and weight documentation . These studies demonstrated that increased knowledge (staff education), capabilities (scales in each clinic room) and reliance on memory (electronic prompting to record weight) significantly improved documentation .…”
Section: Introductionmentioning
confidence: 99%
“…Two recent papers from the same institution used an implementation science approach to address identified barriers to GWG guideline adherence and weight documentation . These studies demonstrated that increased knowledge (staff education), capabilities (scales in each clinic room) and reliance on memory (electronic prompting to record weight) significantly improved documentation .…”
Section: Introductionmentioning
confidence: 99%
“…It has been clearly demonstrated that interventions which include dietary advice, and physical activity, supported by ongoing weight monitoring can prevent excessive GWG and result in more women across all BMI categories achieving weight gain within correct ranges . It may be suggested that this increase in appropriate GWG is a result of service wide changes and support, including guidance provided by dietitians …”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53] It may be suggested that this increase in appropriate GWG is a result of service wide changes and support, including guidance provided by dietitians. 31 Study strengths included the use of an implementation science framework (KTA Framework 13 ) to guide service development and evaluation and our use of the same survey for both cohorts. The recruitment method and response rate are both a strength and a limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have limited population-level estimates on how much information patients receive from clinicians regarding GWG using the most recent IOM guidelines. However, recent research has shown that improving clinician knowledge and effort to address appropriate GWG has been effective in helping women gain within IOM recommendations (Lindberg et al, 2016; Wilkinson et al, 2016). In addition, strategies such as meeting dietary and physical activity goals have been shown to help women gain within IOM recommendations (Muktabhant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%